Treatment of Membranous Nephropathy in Patients With THSD7A Antibodies Using Immunoadsorption - Weinmann-Menke, Julia; Holtz, Stefan; Sollinger, Daniel; Dörken, Mara; Boedecker, Simone; Schamberger, Beate; Pfister, Frederick; Amann, Kerstin Ute; Lutz, Jens (American Journal of Kidney Diseases, 2019)
Antibodies against THSD7A (thrombospondin type 1 domain-containing protein 7A) have been proposed to play a causal role in the development of nephrotic syndrome in patients with THSD7A antibody–positive membranous nephropathy. We hypothesized that removal of these antibodies from plasma could lead to a rapid reduction in proteinuria. Using immunoadsorption to reduce THSD7A antibodies led to a rapid reduction in proteinuria in 2 patients with THSD7A antibody–positive membranous nephropathy. Moreover, our findings support and strengthen the pathogenic role of the antibodies in the development of nephrotic syndrome in patients with THSD7A antibody–positive membranous nephropathy. Taken together, these 2 cases suggest that immunoadsorption could be a useful tool in the treatment of patients with THSD7A antibody–positive membranous nephropathy.
CRIS-Team Scopus Importer:2019-08-30
Keywords: autoantibodies; case report; immunoadsorption; kidney biopsy; malignancy-associated MN; membranous nephropathy (MN); nephrotic syndrome (NS); proteinuria; THSD7A (thrombospondin type 1 domain-containing protein 7A); urinary protein-creatinine ratio (UPCR)